Envoi: A diptych - Elsner, J; Henderson, J (Wilhelm Fink, 2017)
This chapter offers a final reflection on the volume and its themes, taking the form of a ‘diptych’: the first section (by Jaś Elsner) discusses aspects of the Roman resonance of Optatian’s corpus for students of late antiquity today; the second section (by John Henderson) plays out by reviewing Optatian’s razzle-dazzle from a more literary angle, including discussions of Carm. 5 and 14.